Health Equity and Universal Provision in Norway: A Case Study - Lydia Mehrara; Susan Young (Nordic Journal of Social Research, 2020)
This article reports on a qualitative study undertaken to explore the policy-practice nexus of health policy in Norway in relation to the provision and delivery of maternal health services to migrant women.  The research used a case study approach focusing on a particular programme which provided maternal health services to migrant women and collected data through review and analysis of policy documentation, observation of this programme, and discussions with people responsible for implementing health policy.  While Norway is well known for its universal policy principles, which in the main enable good access to services, the case study indicated that there are some limitations in policy and practice.  We use the principle of proportionate universalism to comment on and make recommendations for policy makers and practitioners in this area, to better attend to the principle of equity in service access and usage.  The article provides an overview of the Norwegian health policy systems, structures and provisions; describes the service provision from a specific programme providing maternal health services to migrant women in Stavanger, Norway; and concludes with some recommendations which emerge from the findings.